Internal and External Factors Influencing Waste Sorting Practices: A Behavioral Study at Higher Education - Dinda Sandikta Putri; Muhammad Khairunnazmi; Muhammad Artdiaz Agvito Latif; Abdullah Ramadhan; Muhammad Ariq Fauzi (JRSI (Jurnal Rekayasa Sistem dan Industri), 2025)
This study examines both internal and external factors that affect students' waste sorting behavior at Telkom University, an academic institution that struggles with sorting compliance even after establishing "green campus" initiatives into place. The study used a quantitative correlational approach, surveyed 135 undergraduate students, and used the Theory of Planned Behavior (TPB) to analyse the structural correlations that emerged using PLS-SEM. The model looked at how a student's intention and subsequent sorting behavior were influenced by internal (attitude, subjective norms, perceived behavioral control) and external (information, policy, infrastructure/facility) factors. The findings demonstrated that sorting intention is substantially and favourably predicted by every investigated factor. Accordingly, intention turned out to be an exceptionally strong predictor of actual behaviour (Path Coefficient = 0.726). Importantly, compared to external support (0.261), internal motivation (0.327) has shown a stronger direct impact on intention. The results highlight the necessity of a symbiotic approach to effective, long-term waste management: fostering strong pro-environmental attitudes and societal norms while also offering accessible infrastructure, clear information, and supporting institutional rules and regulations.